The Impact of Unemployment on the Economy in Indonesia - Lenny Yanthiani (Fakultas Ekonomi dan Bisnis Islam, 2022)
The Open Unemployment Rate (TPT) is an indicator that can be used to measure the level of supply of labor that is not used or not absorbed by the labor market. However, compared to conditions a year ago, TPT decreased by 0.58% percent from 7.07% to 6.49%. The phenomenon of unemployment is still an interesting problem to study and study in accordance with economic developments in society. By using qualitative research methods with a deductive thinking approach. This research shows that unemployment occurs because, among other things, the number of jobs available is smaller than the number of job seekers. Also, the competence of job seekers is not in line with the job market. In addition, there is also a lack of effective job market information for job seekers.